A Comparative Study of Synchronous vs. Asynchronous Technology Tools in Developing Oral Communication Skills - Milimo Mundia (Universal Teaching and Learning Journal, 2026)
Purpose: This study explores how synchronous and asynchronous tools contribute to the development of oral communication skills by investigating their impact on fluency, interpersonal understanding, anxiety reduction, and repeated practice. Research Methodology: A mixed-methods approach was used, combining quantitative data from surveys and performance assessments with qualitative insights from interviews, classroom observations and student reflections. Results: Synchronous tools such as Zoom and Microsoft Teams enhanced students' fluency, spontaneity, and interaction skills. In contrast, asynchronous tools, such as Flipgrid and online discussion boards, offered a reflective space that reduced anxiety, allowing for thoughtful and precise contributions. Conclusions: This study emphasizes the importance of hybrid learning methods that combine the strengths of both synchronous and asynchronous approaches to foster confident and accurate communication skills. Limitations: This study was limited to undergraduate students and focused on specific tools, potentially limiting its generalizability to other contexts or educational levels. Contributions: This research highlights the complementary role of synchronous and asynchronous tools in developing oral communication skills, advocating hybrid pedagogies in digital learning environments.